Pulmonary histoplasmosis on the Chinese mainland: two case reports and literature review - Qi Chen; Wei Guo; Wenjia Guo; Xiangdong Mu; Jun Guo (Journal of Infection in Developing Countries)
Introduction: Pulmonary histoplasmosis is a fungal disease that is endemic in North and Central America. It is relatively rare in China and commonly misdiagnosed as tuberculosis or cancer due to nonspecific clinical and radiographic manifestations. Rapid and accurate pathogen tests are critical for the diagnosis of pulmonary histoplasmosis.